A multi-criteria decision making model for outsourcing maintenance services. Issue 3 (2nd March 2015) - Hassanain, Mohammad A.; Assaf, Sadi; Al-Hammad, Abdul-Mohsen; Al-Nehmi, Ahmed
Abstract : Purpose: – The purpose of this paper is to present the development of a multi-criteria decision-making model for use by maintenance managers to consider before making a decision on outsourcing. Design/methodology/approach: – Thirty-eight factors were identified for outsourcing maintenance services. These factors were grouped under six categories, namely: "strategic", "management", "technological", "quality", "economic" and "function characteristics". The Analytic Hierarchy Process, as a multi-criteria decision-making model, was introduced and applied as an approach for maintenance managers in Saudi Arabian universities to consider before making a decision on outsourcing. A case study on the outsourcing decision of maintenance services of air-conditioning systems was carried out to apply the developed model. Findings: – Data analysis indicated that all outsourcing decision groups of factors have almost equal weight, with the "quality" group of factors having the highest weight and the "technological" group of factors having the least weight. Further, the analysis indicated, in general, that the recommended decision for the maintenance managers is to outsource. However, an application of the developed model through a case study on the outsourcing of maintenance services of air-conditioning systems showed that the recommended action is not to outsource. Originality/value: – The presented approach in this paper could be of practical benefit to maintenance managers in their decision making of whether or not to outsource maintenance services. The factors in the model were identified through a literature survey of research carried out in different countries. Therefore, the model could be applied in different settings, depending on the relative weight of the factors by the users.